Alpha brain oscillations, approach attitude, and locus of control affect self-perception of social efficacy in cooperative joint-action. Issue 1 (1st January 2018) - Balconi, Michela; Vanutelli, Maria Elide
ABSTRACT: The neurophysiological basis of social ranking perception underlying the execution of cooperative joint-actions was explored in the present study. Self-perception of social ranking, personality trait (Behavioral Activation System (BAS) and locus of control (LoC)) and alpha brain oscillations were considered. Subjects were required to match their cognitive performance in terms of accuracy (error rate) and response time. A positive feedback condition of a better joint-performance was provided and compared to absence of feedback. It was found that higher BAS participants and higher internal LoC responded in greater measure to post-feedback condition with better real performance probably based on their sensitivity to rewarding for high-BAS and the increased sense of self-efficacy. Moreover, higher-BAS showed an increased frontal left activity when they perceived increased cooperative efficacy. The present results confirmed the tendency to modulate both self-perceived social position and real performance based on the personal attitudes and the frontal.